2002
DOI: 10.1210/jcem.87.6.8739
|View full text |Cite
|
Sign up to set email alerts
|

The Tissue Distribution of the mRNA of Ghrelin and Subtypes of Its Receptor, GHS-R, in Humans

Abstract: Ghrelin is a novel growth hormone-releasing peptide, originally identified in the rat stomach as the endogenous ligand for the growth hormone secretagogue-receptor (GHS-R1a). Ghrelin is involved in the regulation of GH release, but it has recently been suggested that ghrelin may have other actions, including effects on appetite, carbohydrate metabolism, heart, kidney, pancreas, gonads, and cell proliferation. The distribution of ghrelin, its functional receptor (type 1a) and the unspliced, non-functional GHS-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
342
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 995 publications
(363 citation statements)
references
References 0 publications
15
342
0
6
Order By: Relevance
“…In addition, when activated, T cells also express the preproghrelin protein and produce and secrete both acylated and unacylated ghrelin (Baatar et al 2011;Dixit et al 2004). Besides lymphocytes, ghrelin mRNA was also found in human spleen, lymph nodes, and thymus (Dixit et al 2004;Gnanapavan et al 2002). In thymus, ghrelin and the GHS-R1a decline with age.…”
Section: Ghrelin and Ghs-r1a Mrna Expression And Distribution In The mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when activated, T cells also express the preproghrelin protein and produce and secrete both acylated and unacylated ghrelin (Baatar et al 2011;Dixit et al 2004). Besides lymphocytes, ghrelin mRNA was also found in human spleen, lymph nodes, and thymus (Dixit et al 2004;Gnanapavan et al 2002). In thymus, ghrelin and the GHS-R1a decline with age.…”
Section: Ghrelin and Ghs-r1a Mrna Expression And Distribution In The mentioning
confidence: 99%
“…Also GHS-R1a is widely expressed in the lymphoid system, and its expression was reported in the same cells expressing ghrelin (Dixit et al 2004;Hattori et al 2001), as well as in the spleen (Gnanapavan et al 2002). A truncated inactive GHS-R1b has been shown in various immune tissues, although ghrelin does not bind to and activate it and the role of this receptor is still unknown (Taub 2008).…”
Section: Ghrelin and Ghs-r1a Mrna Expression And Distribution In The mentioning
confidence: 99%
“…2002). Rather, AG is thought to potentially interact with the corticotropin‐releasing factor (CRF‐2) receptor in muscle (Filigheddu et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanisms by which ghrelin may influence muscle function may not only be related to an indirect endocrine action GHmediated. It has recently been described that ghrelin, either acyl and des-acyl ghrelin, may act at the muscle level through direct mechanisms not involving GHSR1a receptor which is not present in myocytes (Baldanzi et al 2002;Filigheddu et al 2007;Gnanapavan et al 2002;Sheriff et al 2012). Filigheddu et al (2007) have shown that both ghrelin and des-acyl ghrelin stimulate tyrosine phosphorylation of several muscle proteins and activate ERK-1/2 and Akt, indicating that both ghrelin isoforms could exert a biological activity on muscle cells.…”
Section: Discussionmentioning
confidence: 99%